PF24 and training for teachers: a workshop approach proposal - Andreini, Claudia; Valtancoli, Barbara (Form@re - Open Journal per la formazione in rete, 2018)
Universities have a key role in the initial training for teachers, therefore they can contribute to innovate school, e.g. by proposing students-centered teaching. This article presents the chemistry course activated by the University of Florence as part of the PF24 programme. The course presented contents that were inspired by the most advanced research in chemistry teaching through a problem-based and laboratory approach. The course has obtained good results both in terms of interest shown by attendants and objectives achieved. PF24 e formazione docenti: una proposta di approccio laboratoriale Le Università giocano un ruolo essenziale nella formazione iniziale dei docenti, potendo così contribuire al cambiamento della scuola dal suo interno e all’introduzione di didattiche incentrate sugli studenti. In questo articolo si presenta il corso di didattica della chimica attivato dall’Università di Firenze nell’ambito del PF24. Il corso ha presentato contenuti ispirati alla più aggiornata ricerca in didattica della chimica attraverso un approccio problem-based e laboratoriale. Il corso ha ottenuto buoni risultati sia in termini di interesse mostrato dagli studenti frequentanti sia in termini di obiettivi raggiunti.